Vascular lesions of the breast: Essential pathologic features and diagnostic pitfalls - Huina Zhang; Bradley M. Turner; Hani Katerji; David G. Hicks; Xi Wang (Elsevier, 2021)
Vascular lesions are uncommonly encountered in the breast and they represent a spectrum of benign, atypical and malignant entities. The mammary angiosarcomas can be primary arising de novo, or most frequently secondary to prior radiation therapy for breast carcinoma. There is significant overlap in pathologic features between vascular lesions and their non-vascular mimics, as well as between benign vascular lesions and their malignant counterparts, resulting in diagnostic dilemma, especially in the core biopsy setting. In this article, we review the clinico-radiological findings, pathologic features, role of ancillary testing as well as the management and prognosis of breast vascular lesions, with emphasis on essential pathologic features and potential diagnostic pitfalls.